Drivers of Extinction Risk in Terrestrial Vertebrates. Issue 2 (1st February 2017) - Ducatez, Simon; Shine, Richard
Abstract: Rising rates of extinction create an urgent need to identify the mechanisms and drivers of endangerment. One critical question is whether major phylogenetic lineages are equally at risk to the same threats. We used the IUCN Red List classification to explore the effect of four major threatening processes (habitat alteration, invasive species, climate change and overexploitation) on 7, 441 species in four terrestrial vertebrate classes. As expected, species rated as vulnerable to a higher number of threats were also at greater risk of extinction. However, this pattern differed strongly among classes. Notably, invasive species and climate change were strongly associated with increased risk of extinction in birds but not mammals. These large‐scale differences might be artifacts of differing methodologies used by class specialists to classify species vulnerability; or might reflect biological differences. That ambiguity needs to be resolved, because it has strong implications for the assessment and amelioration of threatening processes.